Implementasi Surat Perintah Membayar Berbasis Kinerja pada Sektor Publik di Indonesia - Nasution, Dito Aditia Darma; Supraja, Galih; Damanik, Annisa Fajariah (E-Jurnal Akuntansi; Vol 32 No 6 (2022)DO - 10.24843/EJA.2022.v32.i06.p07, 2022)
The research aims to discuss the extent to which the implementation of performance-based pay warrants, especially in terms of salaries (salaries and allowances) in the public sector in Indonesia and the consequences that will arise. The methodology used is a literature review, with techniques outlined from Wolfswinkel, Furtmueller, and Wilderom (2011). The results of the study explain that the payroll design in Indonesia adheres to a single payroll pattern consisting of elements of salary and benefits (performance and cost) and it is also found that the consequence of a performance-based pay order in the payroll element is that there is still a gap between Ministries, Institutions and Regional Agencies in providing performance allowance. It was also found that there was no significant improvement in public services, especially direct benefits to the community. This is evidenced by the slow graph of the increase in the community satisfaction index in terms of public services. Keywords: Performannce-based Payment Orders; Salaries; Allowances.